Social-ecological drivers of metropolitan residents’ comfort living with wildlife - Haight, Jeffrey D.; Larson, Kelli L.; Clark, Jeffrey A. G.; Lewis, Jesse S.; Hall, Sharon J. (Frontiers in Conservation Science, 2023)
Human-wildlife coexistence in cities depends on how residents perceive and interact with wildlife in their neighborhoods. An individual's attitudes toward and responses to wildlife are primarily shaped by their subjective cognitive judgments, including multi-faceted environmental values and perceptions of risks or safety. However, experiences with wildlife could also positively or negatively affect an individual's environmental attitudes, including their comfort living near wildlife. Previous work on human-wildlife coexistence has commonly focused on rural environments and on conflicts with individual problem species, while positive interactions with diverse wildlife communities have been understudied. Given this research gap, we surveyed wildlife attitudes of residents across twelve neighborhoods in the Phoenix Metropolitan Area, AZ to ask: how do the environments in which residents live, as well as their values, identities, and personal characteristics, explain the degree to which they are comfortable living near different wildlife groups (coyotes, foxes, and rabbits)? We found that residents who were more comfortable living near wildlife commonly held pro-wildlife value orientations, reflecting the expectation that attitudes toward wildlife are primarily driven be an individual's value-based judgements. However, attitudes were further influenced by sociodemographic factors (e.g., pet ownership, gender identity), as well as environmental factors that influence the presence of and familiarity with wildlife. Specifically, residents living closer to desert parks and preserves were more likely to have positive attitudes toward both coyotes and foxes, species generally regarded by residents as riskier to humans and domestic animals. By improving understanding of people's attitudes toward urban wildlife, these results can help managers effectively evaluate the potential for human-wildlife coexistence through strategies to mitigate risk and facilitate stewardship.